Association of COVID‐19 with skin diseases and relevant biologics: a cross‐sectional study using nationwide claim data in South Korea. (1st February 2021) - Cho, S.I.; Kim, Y.E.; Jo, S.J.
Summary: Background: As the coronavirus disease 2019 (COVID‐19) pandemic has spread, information about COVID‐19 and skin disease or related biologics is still lacking. Objectives: To identify the association between COVID‐19 and skin diseases or biologics. Methods: A nationwide claim dataset relevant to COVID‐19 in South Korea was analysed. This dataset included insurance claim data before and during COVID‐19 treatment and clinical outcomes. Claim data related to skin diseases and relevant biologics were analysed to determine the association of COVID‐19 with skin diseases and relevant biologics. Results: The dataset contained a total of 234 427 individuals (111 947 male and 122 480 female) who underwent COVID‐19 testing. Of them, 7590 (3·2%) were confirmed as having COVID‐19, and 227 (3·0%) confirmed patients died. Among various skin diseases and biologics, no significant increase in the presence of specific skin diseases or exposure to biologics was observed in the COVID‐19‐positive group, even after adjusting for or matching covariates. The presence of skin diseases and exposure to biologics also did not seem to affect clinical outcomes including mortality. Conclusions: Underlying skin diseases did not appear to increase susceptibility to COVID‐19 or mortality from COVID‐19. Considering the risks and benefits, biologics for dermatological conditions might be continuously used during the COVID‐19 pandemic.